Application of thiol capped ZnS quantum dots as a fluorescence probe for determination of tetracycline residues. (1st February 2023) - Mili, Khawla; Hsine, Zouhour; Chevalier, Yves; Ledoux, Gilles; Mlika, Rym
Abstract: A new rapid and sensitive fluorescence probe based on zinc sulfide (ZnS) quantum dots (QDs) as an eco-friendly alternative has been produced for the detection of tetracycline (TCy). ZnS QDs have been innovatively prepared via simple aqueous colloidal method with thioglycolic acid (TGA) as a stabilizer and characterized by infrared spectroscopy, X-ray diffraction, transmission electron microscopiy, UV–Visible absorption and photoluminescence spectroscopy. The blue shift of the absorption band and bandgap values with respect to that of bulk ZnS materials confirms the quantum confinement effect. IR spectra show the binding of TGA to the surface of ZnS QDs. X-ray diffraction confirms the formation of a cubic phase of ZnS. Temperature-dependent photoluminescence (PL) spectroscopy shows three emission bands at 405 nm, 442 nm and 483 nm ascribed to electronic transitions involving Zn and S vacancies and interstitial sites. TGA-ZnS QDs is. able to detect TCy in an aqueous medium with a pH compatible with the pH of biological fluids which highlight the flexibility and applicability of this sensor in real media. Regarding TCy detection by QD fluorescence, a linear relationship of fluorescence intensity and TCy concentration is obtained over the wide range of 25–6000 nM, and the limit of detection (LOD) is as low as 0.03 nM. Thanks to its excellent analytical performance, such ZnS QDs fluorescent probe is a promising sensing platform for the analysis of trace TCy in biological fluids. Current probe was applied for TCy quantification in milk samples with superior results. Highlights: Highly fluorescent TGA-ZnS QDs are synthesized by simple aqueous route. The Synthesized TGA-ZnS QDs have spherical shapes with good solution dispersibility. TGA-ZnS QDs were innovatively used for detection of tetracycline. TGA-ZnS sensor shows a good sensitivity for the TCy with a lower detection limit. Tetracycline antibiotic in milk samples can be detected with excellent accuracy.